Experimental Comparison of Functionality between the Main Types of Methane Measurement Sensors in Mines - José Luis Lorenzo-Bayona; David León; Isabel Amez; Blanca Castells; Ljiljana Medic (Energies, 2023)
In recent years, coal mine methane measurement techniques in mines have been gaining importance as poor firedamp control in work can cause the interruption of production and even fatal accidents. Since there is currently a variety of methane measurement equipment with different functional characteristics and measurement principles, a study is needed to indicate which type of equipment has the highest degree of confidence. This research presents the results of a study carried out by the Official Laboratory J. M. Madariaga (LOM) of the Polytechnic University of Madrid that aims to analyze the reliability of methane detection systems used in underground mining. Therefore, a series of portable and non-portable methane detectors with different measurement principles have been selected to subject them to laboratory tests following the methods described in the applicable regulations, such as time of response, dust effect, temperature, pressure, etc. The test equipment is usually the one used in the certification and calibration of these devices, subject to the LOM quality system. The results of these tests allowed for defining a marking system that led to a ranking of the tested methane detectors in order to find the advantages and disadvantages of each type. From the performed tests, a summary of the main sources of sensor inaccuracy was reported. It was found that catalytic sensors might present significant deviations when testing high concentrations in short periods of time or low concentrations during long periods of time. On the other hand, devices with an interferometric sensor can be unreliable as the measures are very sensitive to changes in environmental conditions, and optical sensors present longer response times than catalytic sensors.